Applicative constructions - Peterson, David A. (David August), 1968- (Oxford studies in typology and linguistic theory., 2007)
This book presents a typological analysis of applicatives across African, American Indian, and East Asian languages. It also addresses their functions in discourse, the derivation of their semantic and syntactic properties, and how and why they have changed over time.